2019
DOI: 10.1002/evl3.119
|View full text |Cite
|
Sign up to set email alerts
|

Extended haplodiploidy hypothesis

Abstract: Evolution of altruistic behavior was a hurdle for the logic of Darwinian evolution. Soon after Hamilton formalized the concept of inclusive fitness, which explains how altruism can evolve, he suggested that the high sororal relatedness brought by haplodiploidy could be why Hymenopterans have a high prevalence in eusocial species, and why helpers in Hymenoptera are always female. Later it was noted that in order to capitalize on the high sororal relatedness, helpers would need to direct help toward sisters, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…; Quinones & Pen ; Rautiala et al . ). It remains equivocal, however, whether relatedness really was unusually high in the ancestors of today's eusocial taxa (Nonacs ; Pernu & Helantera ), and the ecological parameters in Hamilton's Rule are potentially just as important determinants of whether helping or solitary nesting is the optimal strategy (Queller , ; Field et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Quinones & Pen ; Rautiala et al . ). It remains equivocal, however, whether relatedness really was unusually high in the ancestors of today's eusocial taxa (Nonacs ; Pernu & Helantera ), and the ecological parameters in Hamilton's Rule are potentially just as important determinants of whether helping or solitary nesting is the optimal strategy (Queller , ; Field et al .…”
Section: Introductionmentioning
confidence: 97%
“…Starting with Hamilton's (1964) famous threequarters relatedness hypothesis, theoretical attempts to understand why eusociality evolved in Hymenoptera have tended to focus on factors that can raise genetic relatedness such as haplodiploidy and more recently, lifetime queen monogamy (e.g. Trivers & Hare 1976;Seger 1983;Boomsma 2009;Fromhage & Kokko 2011;Nonacs 2011Nonacs , 2014Gardner et al 2012;Quinones & Pen 2017;Rautiala et al 2019). It remains equivocal, however, whether relatedness really was unusually high in the ancestors of today's eusocial taxa (Nonacs 2011;Pernu & Helantera 2019), and the ecological parameters in Hamilton's Rule are potentially just as important determinants of whether helping or solitary nesting is the optimal strategy (Queller 1994(Queller , 1996Field et al 2000;Korb & Heinze 2008;Avila & Fromhage 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In general, genetic relatedness promotes cooperation and increases contributions to collective action. For examples, both theoretical and empirical research on the evolution of cooperative breeding in haplodiploids suggest that cooperation is more likely to evolve under monogamy than when broods are the result of polyandrous matings (2326); in theoretical work that specifically asks whether males or females should evolve into helpers, monogamous situations under haplodiploidy can favour females as helpers (9, 27). Our results add a collective action angle to these results: ours is not a model of cooperative breeding, as in our setting no individual foregoes own reproduction to help others, instead the collective good is group survival up to maturity.…”
Section: Discussionmentioning
confidence: 99%
“…However, a very recent theoretical analysis has concluded that this logic is incomplete [11]. In this reanalysis, split sex ratios are unnecessary for the haplodiploidy hypothesis to work, as long as altruists preferentially rear sisters over brothers (i.e., through manipulating their nest's sex ratio), and altruism is still favored at a 3:1 population sex ratio.…”
Section: The Haplodiploidy Hypothesis Makes a Comeback?mentioning
confidence: 94%